Dual Targeting to Overcome Current Challenges in Multiple Myeloma CAR T-Cell Treatment - van der Schans, Jort J.; van de Donk, Niels W. C. J.; Mutis, Tuna (Frontiers in Oncology, 2020)
In the era of highly promising novel targeted-immunotherapy strategies for multiple myeloma (MM), the first series of clinical trials with CAR T-cells targeting the plasma cell-specific B-cell maturation antigen (BCMA) have shown excellent response rates. In the long-term, however, MM appears to escape the therapy likely due to initial low and heterogeneous expression or downregulation of BCMA expression. Several other molecules targeted by CAR T-cells in MM are expressed at high levels on MM cells, but many of these attractive targets are also expressed on various, sometimes vital nonmalignant cells, posing major risks for on-target, off-tumor side effects. CAR T-cell therapy for MM therefore faces two urgent challenges: i) improving the efficacy of BCMA CAR T-cells and ii) establishing a MM-selectivity even when CAR T-cells are directed against not entirely MM-specific target antigens. In this review we will outline the current attempts to tackle these challenges, with a specific focus on how dual CAR targeting might be applied to tackle both issues.